Synthesis, Hirshfeld Surfaces and Characterization of Diethanolaminium 3,5-dinitrosalicylate single crystal for NLO application - B Shanmuga Priya; D. Rajan Babu (Results in Physics)
A novel organic Diethanolaminium 3,5-dinitrosalicylate was obtained at room temperature from an equimolar solute concentration in Millipore water. The resulting crystal crystallized in the Triclinic P −1 system. Examining the Hirshfeld Surfaces confirms the presence of π-π stacking in the molecule. The 2D fingerprint plots obtained by the analysis of HS provide information regarding various interactions contributing to crystal packing. A review of the spectrum produced by FTIR spectroscopy was conducted to analyze the frequencies associated with functional groups. NMR studies detected the different Carbon and Hydrogen atoms in distinct chemical environments. The optical studies suggest that the obtained crystal shows low absorption in the 450––750 nm region with 2.55 eV corresponding to direct bandgap. The crystal’s refractive index is calculated as 1.693. A high HOMO-LUMO gap value indicates stability and less reactivity of the material. The synthesized material decomposes above 205 °C. The analysis of Z-Scan revealed that the third-order susceptibility was 3.726 × 10-8 esu. The Z-Scan analysis reveals the Reverse Saturable Absorption and self-defocusing behavior of DANS.